Exploring the Role of Memrise in Enhancing EFL Learners’ Motivation - Halimah, Nur; Pujiani, Tri (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2025)
Student motivation has always been an obstacle within English as a Foreign Language (EFL) teaching and it continues to be a technological barrier with learners at the beginner level. This study investigates the impact of the gamified, mobile-assisted language learning application, Memrise, on students’ motivation to learn English. The study aimed to provide insight into what the effective extent of Memrise is and how it can promote learner motivation within EFL environments. This study used a pre-experimental one-group pretest-posttest design, with 28 first-year university students enrolled in a Beginner English 2 course at a university in Indonesia. Data for the study were collected using observations, structured questionnaires informed by Self-Determination Theory and Connectivism, and semi-structured interviews. Quantitative data were analyzed descriptively and using paired sample t-tests, and qualitative data were analyzed thematically. The findings demonstrated a statistically significant improvement in students' motivation after the Memrise intervention, and the students reported higher autonomy, competence, and engagement than before the intervention. The additional features, including chatbot conversations, real-time feedback, and progress tracking, helped to facilitate the improved levels of motivation. The paper argues that Memrise is an effective strategy for encouraging sustainable motivation in EFL learners and contributes to the ongoing discourse on mobile learning, presenting practical implications for educators and app developers to consider as they develop increasingly engaging and learner-centered digital environments.